2019
DOI: 10.1002/cbic.201900152
|View full text |Cite
|
Sign up to set email alerts
|

Compartments for Synthetic Cells: Osmotically Assisted Separation of Oil from Double Emulsions in a Microfluidic Chip

Abstract: Liposomes are used in synthetic biology as cell-like compartments and their microfluidic productiont hrough double emulsions allows for efficient encapsulationo fv arious components. However,r esidual oili nt he membrane remains ac riticalb ottleneck for creating pristine phospholipid bilayers. It has been discovered that osmotically driven shrinkingl eads to detachment of the oil drop. Separation inside am icrofluidic chip has been realizedt oa utomate the procedure, which allows for controlled continuous pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…Shearing/squeezing, as well as surface tension minimization are believed to be the main drivers of the separation of the double emulsion in OLA [ 14 ]. Krafft et al have recently demonstrated that osmotic shrinking can enhance the separation of oil droplets from GUVs in other microfluidic double emulsion techniques [ 61 ]. This may be used in future studies to investigate whether or not this effect can also be used for improving the separation of the octanol pocket in OLA derived vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Shearing/squeezing, as well as surface tension minimization are believed to be the main drivers of the separation of the double emulsion in OLA [ 14 ]. Krafft et al have recently demonstrated that osmotic shrinking can enhance the separation of oil droplets from GUVs in other microfluidic double emulsion techniques [ 61 ]. This may be used in future studies to investigate whether or not this effect can also be used for improving the separation of the octanol pocket in OLA derived vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…With this design, Deshpande et al [335] used an octanol-assisted system to construct a coacervate-in-liposome system. Krafft et al [347] developed a method to de-wet a vesicle fabricated in a w/o emulsion, using an osmotic gradient composed of sucrose and sodium chloride. Even triple emulsions can be prepared by means of droplet generator microfluidics.…”
Section: Microfluidics-based Techniques To Fabricate Protocellsmentioning
confidence: 99%
“…These aqueous phases impede the use of centrifugation as a purification method. As an alternative, Krafft and coworkers developed a simplified system relying solely on sucrose/salt solution as the inner and outer aqueous phases [58]. To completely dewet the Droplet-based microfluidics features various functional units: a droplet production unit to encapsulate a variety of chemical and biochemical contents [26]; a pico-injector for the sequential injection of picoliter volumes into individually produced droplets [94]; a fusion module to provoke the fusion of two distinct droplets, thus enabling the mixture of various chemical and biochemical reagents with high temporal control [95]; a mixing module to improve convection and thereby facilitate molecular reactions within the droplet [96]; a sorting module to precisely separate individual droplets based on various analytical signals such as fluorescence [62] or mass spectrometry [97]; a releasing unit to liberate the entrapped mixture from the droplet into an aqueous continuous phase by applying an electrical field [98] or by using a passive trapping structure [26]; and a detection or observation module that facilitates the assessment of a large droplet population [43,99].…”
Section: Microfluidic Generation Of Micro-scale and Multicompartment Synthetic Cellsmentioning
confidence: 99%